Assessment of Achievement Motivation for Individual and Team Game Players with Optimistic and Pessimistic Attitude: A Study on the Assessment of Achievement Motivation among Individual and Team Game Players with Different Attitudes (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The purpose of the study was to Study of Assessment of Achievement Motivation for Individual and Team Game Players with Optimistic and Pessimistic attitude. A total of 100 male sports persons from team sports were purposively selected to act as subjects for the purposed study. The age of the subjects ranged between 17 to 30 years and the mean age of the subjects was found to be 21 (+SD) years. The subjects were sports persons from Basketball (20), Boxing (20), Cricket (20), Netball (20) and Hockey (20) with minimum Inter University level participation in their respective sports discipline. The questionnaire developed by D.S. Parasar (1998), Dr. M.L. Kamlesh, 1990 and Agashe and Helode, 2002 were used for assessing the Optimistic attitude, Sports achievement and emotional intelligence of the sports persons. The data for the present study was collected through the administration of the selected test items for psychological variables on the selected Inter varsity players from all over Haryana. The collected data was analyzed by computing Descriptive statistics, Independent t-test followed by Pearson’s Product moment correlation. The level of significance was set at 0.05 levels.